Men of Letters: W.B. Yeats’s A Packet for Ezra Pound (1929) - Adrian PATERSON (E-REA)
If Bakhtin’s “dialogic imagination” suggests the novel’s discourse is structured to expect an answer, Yeats’s dialogic imagination is best expressed in non-fictional prose. Acting as preface to A Vision (1937), as published in 1929 by Cuala Press, A Packet for Ezra Pound asserts an often overlooked independent existence. Considering it formally alongside Yeats’s letters as a bookish yet speech-driven manifesto, this paper argues that what appears as a provisional, peripheral, prefatorial work is nonetheless central to understanding Yeats and Pound’s evolving thinking, and critical to an understanding of modernist networks. Its genre-bending, pan-artistic vision, intertextuality, and playing with paratextual apparatus produces a self-conscious construction typical of modernism, even as it claims distance from modernist aesthetics and dissents from its politics.